PERKEMBANGAN WATAK LIRA DALAM NOVEL TO KILL A KINGDOM OLEH ALEXANDRA CHRISTO - Wibowo, Refa Anafdariska; Fanani, Abu; Romdlon, Atiq Mohammad; Rohman, Abdur; Frank, Ahmad (Universitas Nusantara PGRI Kediri, 2025)
This study was to analyze the character growth of a unique character of Lira in Alexandra Christo’s To Kill a Kingdom. It is regarded as a unique character as Lira is not just character. She undergoes a transformation from a rude animal to good human being. Not like the change of character of a man whose changes only from bad to good character without anatomic change, Lira has to face problems to become a good person. Using close reading, the researcher is able to explore deeply the character of Lira before changing and after changing into a human with the result that after taking pains to overcome the problems, Lira is able to change her personality from bad ones: bloodthirsty and obedient (to bad things) to good ones: merciful, disobedient (to bad things), selfless, and noble person. Though the six determinants of Hurlock play important role for the character change, however, the researcher highlights that the more important ones are within somebody himself/herself. Therefore, the six determinants of Hurlock need attention to be more paid because the person plays a role in the world. Thus, the world is a stage within which there are many roles played so that people should be careful to play their roles in this stage.